A cointegration model of money and wealth - Katrin Assenmacher-Wesche; Andreas Beyer (Goethe University Frankfurt, Center for Financial Studies (CFS), 2019)
Extending the data set used in Beyer (2009) to 2017, we estimate I(1) and I(2) money demand models for euro area M3. After including two broken trends and a few dummies to account for shifts in the variables following the global financial crisis and the ECB's non-standard monetary policy measures, we find that the money demand and the real wealth relations identified in Beyer (2009) have remained remarkably stable throughout the extended sample period. Testing for price homogeneity in the I(2) model we find that the nominal-to-real transformation is not rejected for the money relation whereas the wealth relation cannot be expressed in real terms.
urn:nbn:de:hebis:30:3-480560
Keywords: E41; C32; C22; 330; money demand; wealth; cointegration; vector error correction model; I(2) analysis